An exploration of the judgement of sexual situations by adolescents with autism spectrum disorders versus typically developing adolescents. (April 2017) - Visser, Kirsten; Greaves-Lord, Kirstin; Tick, Nouchka T.; Verhulst, Frank C.; Maras, Athanasios; van der Vegt, Esther J.M.
Highlights: More insight in the factors associated with the development of inappropriate sexual behaviour, sexual problems and sexual victimization in adolescents with autism spectrum disorders (ASD) is required. When asked to judge the appropriateness of different sexual situations, both adolescents with and without ASD accurately identified severely inappropriate sexual situations and adolescents in both groups differed most from the expert panel in their judgement of appropriate (perfectly acceptable) and slightly inappropriate sexual behaviours. Adolescents with and without ASD were mostly more strict (i.e., more conservative) than an expert panel of health care professionals in their judgement of different illustrated sexual situations. Judgement of the appropriateness of paper illustrated sexual situations displaying a wide range of appropriate and inappropriate sexual behaviours does not differentiate between adolescents with and without ASD. Abstract: Background: Inappropriate sexual behaviour, sexual problems and sexual victimization in adolescents with autism spectrum disorders (ASD) is regularly reported in previous research, but little is known about factors associated with these problems, nor about factors associated with a healthy sexuality development in adolescents with ASD. Investigating the judgement of sexual behaviour can be a first step in acquiring insight into inappropriate sexual behaviour in adolescents with ASD. Methods: We assessed how 94 cognitively-able adolescents with ASD and 94 typically developing (TD) adolescents judged the appropriateness of different illustrations of sexual situations and we investigated the differences between the two groups. Results: The highest level of agreement between the judgements of adolescents with ASD and the judgements of an expert panel was found for severely inappropriate sexual behaviours (89.2%) and the lowest agreement was found for appropriate (31.7%) and slightly inappropriate sexual behaviours (26.1%). No significant differences were found between the judgements of the adolescents with ASD and the TD adolescents. Regarding the divergent judgements, adolescents with and without ASD were mostly more strict (i.e., more conservative) than the expert panel in their judgement of sexual situations. Finally, a small percentage of adolescents with and without ASD showed milder (i.e., less conservative) judgements of sexual situations portraying behaviour that was considered severely inappropriate by an expert panel. Conclusions: Our findings showed that, overall, judgement of illustrations of sexual situations does not seem to be hampered in adolescents with ASD. More research is needed to clarify whether this also holds true for their judgements of – and actions in – more complex real life situations.